Tanggung Jawab Perbankan Terhadap Pencairan Kredit Fiktif : Perspektif Keuangan Negara: Banking Responsibility For Fictitious Credit Disbursement: A State Finance Perspective - Dien Nufitasari; Yudho Taruno Muryanto; Jamal Wiwoho; Dwi Tjahja Kusumo Wardhono; Reka Dewantara (Badan Pembinaan dan Pengembangan Hukum Pemeriksaan Keuangan Negara Badan Pemeriksa Keuangan RI, 2026)
The development of the Indonesian banking sector accompanied by an increase in the risk of crime, particularly the disbursement of fictitious credit that is detrimental to customers and state finances. This study aims to examine the limits of banking liability from the perspective of state finance. The method used is normative juridical with legislative, conceptual, case, and comparative approaches. The results of the study show that the accountability of banks as a corporation cannot be limited only to criminal liability, but also includes civil liability through loss recovery and administrative liability as an instrument to strengthen banking compliance and governance. The contribution of this research lies in the development of the State-Finance-Oriented Banking Liability Framework, which is a conceptual framework that integrates the dimensions of preventive liability, restorative liability, and punitive liability in bank accountability for fictitious credit practices that have an impact on state finances. The strengthening of regulations is expected to increase legal certainty, strengthen protection of state finances, and maintain the stability of the national banking system.